Desenvolvimento de formulações à base de D-limoneno para o controle da mosca-branca (Bemisia tabaci) - Marques, Rodrigo Tavares (2021)
The species Bemisia tabaci of whitefly presents commercial relevance in agriculture due to its potential damage to productivity of the different host crops for this pest, like soybean, bean, and tomato. The use of natural insecticide is an important strategy in the control of this pest, with emphasis on essential oils. In this work, three formulations based on D-limonene were developed aiming the control of whitefly. The types of formulations tested were: emulsifiable concentrate, microemulsions, and wet powder. The three formulations presented good stability and similar effectiveness in all agronomic efficiency test. Regarding adult whitefly control, the formulations developed showed results compatible with those of two insecticides available on the market (Talstar® and Sperto®). However, when used in pure form, they presented unsatisfactory results for the control of whitefly nymphs. Based on the performed experiments, on the cost, and flexibility of production, the most suitable formulation was the emulsifiable concentrate type. It is important to mention that, to have effectiveness in controlling adults and nymphs, it must be used with Bifenthrin (Talstar®).